Impact of Hepatic Steatosis, Psoas Muscle Mass, and Density on Outcomes in Patients with Moderately Severe and Severe Acute Pancreatitis: A Serial Computed Tomography-Based Retrospective Study - Jerath, Akhil; Rewari, Nishita; Gupta, Pankaj; Jearth, Vaneet; Singh, Anupam; Shah, Jimil; Samanta, Jayanta; Mandavdhare, Harshal; Sharma, Vishal; Sinha, Saroj K.; Dutta, Usha (Indian Journal of Radiology and Imaging, 2025)
There is limited literature on the association of fatty liver and muscle mass with outcomes of acute pancreatitis (AP) in Indian patients. We aim to investigate the impact of these parameters on clinical outcomes in AP patients based on serial computed tomography (CT) scans.Consecutive patients of AP who had a baseline CT scan within 2 weeks of pain onset and a follow-up CT scan within 2 months of initial CT scan were included. Fatty liver, spleen to liver attenuation difference (AD), psoas muscle area (PMA), and psoas muscle attenuation (PMAt) were assessed on baseline and follow-up portal venous CT scans. Their association with the length of hospitalization, intensive care unit (ICU) admission, length of ICU stay, surgery, and mortality were assessed using univariate and multivariate analysis.One hundred and ninety-eight patients (143 [72.2%] males, mean age 37.9 [ ± 12.4] years) were included. The mean interval between the two CT scans was 30 days (± 13.5 days). Twenty-four (12.1%) patients had fatty liver at baseline CT and 58 (29.3%) patients had fatty liver on follow-up CT (p < 0.001). The mean AD at the baseline scan was –10.2 (± 12.3) Hounsfield units (HU) and on follow up was –18.8 (± 21.7) HU (p < 0.001). PMA in baseline CT was 13.9 (± 5.5) mm2 and on follow-up was 11.2 (± 4.6) mm2 (p < 0.001). PMAt on baseline CT was 49.2 (± 8.2) HU and on follow-up was 47.1 (± 12.1) HU (p < 0.001). In multivariate analysis, the PMA and PMAt were significantly associated with the clinical outcomes. There was no association of fatty liver with clinical outcomes. The parameter with the highest area under the curve for predicting clinical outcomes was PMAt at follow-up CT.Psoas muscle-based assessment is associated with clinical outcomes in patients with AP.
Keywords: acute pancreatitis; computed tomography; fatty liver; psoas muscle area; sarcopenia